Nigella sativa oil: physico-chemical properties, authentication analysis and its antioxidant activity - Rohman, Abdul; Lukitaningsih, Endang; Rafi, Mohamad; Ahmad Fadzillah, Nurrulhidayah; Windarsih, Anjar (Rynnye Lyan Resources, 2019)
Nigella sativa oil (NSO) is one of the high value oils in fats and oils industry due to its nutritional applications and its beneficial effects on human health. Several biological activities have been reported, especially antioxidant activities due to its active components, especially phenolics compounds. Some methods have been used for extraction of NSO from seeds to obtain high yield with excellent quality which includes solvent extraction, cold press, Soxhlet, and microwave assisted extraction. NSO commands a high price in the market, as a consequence, NSO is a target to be adulterated with cheaper oils such as corn and soybean oils. Indeed, the authentication analysis of NSO by determining several physico-chemical properties to determine the characteristics of NSO must be performed. This review highlighted some physico-chemical properties of NSO along with authentication of NSO from adulterants. The antioxidant activities of NSO were also highlighted in this review. Based on its activity as antioxidant, NSO is a good source to be used in nutraceutical and pharmaceutical products.